Implementasi Pendidikan Hukum Sebagai Upaya Pencegahan Tindak Kriminalitas Di Lingkungan Sekolah - Charliesta (CV. SINAR HOWUHOWU, 2025)
This study aims to examine the implementation of legal education as a preventive effort to reduce criminal behavior in school environments. A qualitative approach with a case study method was employed to explore in depth the practice of legal education at a selected public junior high school. Data were collected through in-depth interviews, participatory observation, and document analysis, and were analyzed interactively. The findings indicate that legal education has been integrated into formal classroom instruction, extracurricular activities, and collaborations with local law enforcement. These initiatives have contributed to an increased legal awareness among students and a noticeable reduction in minor offenses such as bullying and verbal abuse. However, challenges remain in the form of limited curriculum time, inadequate teacher competence in legal topics, and insufficient external support. Therefore, legal education should be strengthened systematically to foster students’ legal awareness and social responsibility.